Step (1): Assume given statement
Let the given statement be P(n), i.e.
P(n):(1+11)(1+12)(1+13).....(1+1n)=(n+1)
Step (2): Checking statement P(n) for n=1
Put n=1in P(n), we get
P(1):(1+11)=(1+1)
⇒2=2
Thus P(n) is true for n=1
Step (3): P(n) for n=K
Put n=Kin P(n) and assume this is true for some natural number K i.e.,
P(K):(1+11)(1+12)(1+13)⋯(1+1K)=(K+1) ⋯(1)
Step (4): Checking statement P(n) for n=K+1
Now we shall prove that P(K+1)is true whenever P(K) is true.
Now, we have
(1+11)(1+12)(1+13)⋯(1+1K)(1+1(K+1))
=(K+1)(1+1K+1) (using (1))
=(K+1)(K+1+1K+1)
=((K+1)+1)
Thus, P(K+1) is true whenever P(K) is true.
Final Answer : Therefore, by the principle of mathematical induction, statement P(n) is true for all n∈N.